Of the trend detection problem for a stochastic sequence - Legostayeva, I. (Lithuanian Mathematical Journal, 1972)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: И. Легостаева. К задаче выделения тренда случайной последовательности I. Legostajeva. Apie atsitiktinės sekos trendo išskyrimo uždavinį